Visceral Inflammation and Immune Activation Stress the Brain - Holzer, Peter; Farzi, Aitak; Hassan, Ahmed M.; Zenz, Geraldine; Jačan, Angela; Reichmann, Florian (Frontiers in Immunology, 2017)
Stress refers to a dynamic process in which the homeostasis of an organism is challenged, the outcome depending on the type, severity and duration of stressors involved, the stress responses triggered and the stress resilience of the organism. Importantly, the relationship between stress and the immune system is bidirectional, as not only stressors have an impact on immune function, but alterations in immune function themselves can elicit stress responses. Such bidirectional interactions have been prominently identified to occur in the gastrointestinal tract in which there is a close cross-talk between the gut microbiota and the local immune system, governed by the permeability of the intestinal mucosa. External stressors disturb the homeostasis between microbiota and gut, these disturbances being signalled to the brain via multiple communication pathways constituting the gut-brain axis, ultimately eliciting stress responses and perturbations of brain function. In view of these relationships, the present article sets out to highlight some of the interactions between peripheral immune activation, especially in the visceral system, and brain function, behaviour and stress coping. These issues are exemplified by the way through which the intestinal microbiota as well as microbe-associated molecular patterns including lipopolysaccharide communicate with the immune system and brain, and the mechanisms whereby overt inflammation in the GI tract impacts on emotional-affective behaviour, pain sensitivity and stress coping. The interactions between the peripheral immune system and the brain take place along the gut-brain axis, the major communication pathways of which comprise microbial metabolites, gut hormones, immune mediators and sensory neurons. Through these signalling systems, several transmitter and neuropeptide systems within the brain are altered under conditions of peripheral immune stress, enabling adaptive processes related to stress coping and resilience to take place. These aspects of the impact of immune stress on molecular and behavioural processes in the brain have a bearing on several disturbances of mental health and highlight novel opportunities of therapeutic intervention.